Optimalisasi Kesehatan Anak Panti Asuhan Melalui Pemeriksaan Kesehatan Dasar - richa, fadhila tsania (Journal of Midwifery in Community, 2025)
children are valuable assets of the nation whose physical, mental, and social health must be preserved. Orphanges play a crucial role in providing care and protection, yet they often face challenges related to health facilities and nutrition education. This community service activity aimed to enhance the understanding and awareness of orphanage children regarding the importance of health check-ups. The methods included basic health ecaminations (Body Mass Index, vital signs, and dental check ups), interactive personal education, and recreational activities such as drawing and decorating fruit salads. The activity was conducted with 19 children and early adolescent at Pucang Kerep, Surabaya, in June 2025. Results showed that most children had normal vital signs, 68,4% had normal mutritional status, 21,1% were obese, 5,3% overweight, and 5,3% undernourished. Additionally, 78,9% experienced dental caries, and three early adolescent girls had irregular menstrual cycles consistent with the initial menarche phase. Recreational activities also supported mental health and encouraged healthy lifestyle motivation. Regular health monitoring and the cultivation of clean and healthy living habits are recommended to improve the physical and psychological well being of orphanage children.